Experience of application of extraperitoneal pelvic packing in unstable pelvic ring injuries - I. M. Samokhvalov; I. V. Kazhanov; V. A. Manukovskiy; A. N. Tulupov; S. I. Mikityuk; Ya. V. Gavrishchuk (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. Clinical efficacy of extraperitoneal pelvic packing for hemostasis was assessed in patients with unstable pelvic ring injuries and signs of unstable hemodynamics. MATERIAL AND METHODS. The results of treatment were analyzed in 19 patients with hemodynamically unstable pelvic ring injuries. Extraperitoneal pelvic packing was applied in order to stop bleeding after mechanical pelvic stabilization. The evaluation of hemostasis efficacy was performed by using computerized helical tomography with intravenous contrast. RESULTS. The extraperitoneal pelvic packing allowed doctors to achieve stop of bleeding in 14 (73,7 %) patients. CONCLUSIONS. Complex of mechanical stabilization and extraperitoneal pelvic packing of damaged pelvic ring could be actively used in cases of severe injuries for victims in critical conditions.